Quality of reproductive health care provided by community health centers of a district located in western India- a mixed method study - Misra, Shobha; Desai, Niraj (International Journal Of Community Medicine And Public Health, 2022)
Background: Under National Rural Health Mission in 2007, Indian Public Health Standards (IPHS) were introduced to strengthen health care services. As majority of health infrastructure is in existence before introduction of IPHS, there was scant information available on assessment of these standards. This study was carried out with the objective to assess quality of reproductive health care provided by community health centers (CHC). Methods: A cross-sectional study was carried out in 2013. All of the 17 community health centers from 12 talukas of the district were studied. Data collection was carried out by administering pilot tested checklist and interviewing clients. Results: All the CHCs had adequate infrastructure. Highest score was obtained for input (64%). The overall score in process section was 45%. None of the CHCs had a full-time anesthetist, physician, public health programme manager or public health nurse. At only three CHCs, general surgeon was available. Availability of MOs was 85% and Pharmacist was 88% respectively. Conclusions: Deployment and availability of specialist is the need of the hour. Adequate emphasis needs to be given to processes and outputs as well, apart from inputs. Public private partnership can be explored for better utilization of services. There is a need of up gradation of existing CHCs keeping in the view of IPHS norms.